Late diagnosis of Bowenoid in situ carcinoma in two cats: the importance of identifying mild and superficial lesions - Martins, Nadiene Alves; Moraes, Reiner Silveira de; Romani, Alana Flávia; Araujo, Gustavo Henrique Marques; Cagnini, Didier Quevedo (Brazilian Journal of Veterinary Pathology, 2024)
Cutaneous neoplasms have a significant representation in the casuistry of neoplasms in felines, emphasizing squamous cell carcinoma and basal cell carcinoma. Thus, clinical knowledge is necessary for the correct diagnostic and curative approach to the patient. This study aimed to report two cases of late diagnosis of Bowenoid carcinoma in adult cats (> one year) admitted at the Veterinary Teaching Hospital of the Federal University of Jataí in order to collaborate with the existing literature and help veterinarians in the knowledge of associated lesions. At macroscopy in the hospital admission, both cats presented lesions on the head in the bilateral supraorbital frontal region that slowly evolved into erosions and crusted ulcers with purulent exudation, in addition to lesions in the perilabial region (case 1). In microscopy, findings revealed Bowenoid carcinoma in situ. Supraorbital lesions revealed the abrupt formation of epidermal plaques, including follicular infundibulum continuous with the acanthotic epidermis with loss of normal stratification. Focal orthokeratosis and marked atypia of keratinocytes (macrokaryosis, macronucleosis, macrocytosis, anisokaryosis, and anisocytosis) were also observed. Early diagnosis through clinical analysis combined with histopathological evaluation is of fundamental importance to ensure therapeutic success, improving the patient’s prognosis, a condition not achieved in the cases presented mainly due to late diagnosis.